Public and private pensions in Canada : an economic analysis - Pesando, James E.; Rea, Samuel A. (Toronto; Buffalo: Published for the Ontario Economic Council by University of Toronto Press, 1977)
The adequacy of both public and private pension schemes has become a topic of increasing concern in recent years. The recent increase in the rate of inflation has focused attention on a crucial problem facing private pension plans. Can private pensions provide for the full indexation of benefits with respect to inflation, as do the CPP (Canada Pension Plan) and the superannuation plan for federal civil servants, and yet remain actuarially sound?. The purpose of this monograph is to analyze several of these and other important issues.
Includes bibliographical references: p. [179]-185.
ne 04/05/2018
Loans
Keywords: Old Age Pensions; Canada